Orthopaedic Trainee Views on Robotic Technologies in Orthopaedics: A Survey-Based Study - LeRoy, Taryn E.; Puzzitiello, Richard; Ho, Bridgette; Van Schuyver, Paul R.; Kavolus II, Joseph J. (The Journal of Knee Surgery, 2022)
The use of robotics is a growing area within the field of surgery, especially in orthopaedics. To date, there is no literature examining orthopaedic trainee perception of or comfort with robotics in orthopaedics. An assessment of the next generation's attitudes regarding this technology is necessary. An anonymous, national, web-based questionnaire containing 16 multiple-choice questions and 25 5-point Likert's scale questions was sent to 66 Accreditation Council for Graduate Medical Education (ACGME)-approved orthopaedic residency training programs. The survey was designed to discern the attitude of orthopaedic trainees toward robotics. Demographics, extent of exposure and training, and trainee perception regarding robotics were collected. A bivariate analysis using Pearson's Chi-square test or Fisher's was used to determine factors associated with trainee's future plans to use robotics. A total of 280 trainees completed the survey (response rate of 18%). Also, 67.9% have been exposed to and 42.9% trained to use robotics in surgical training. Of those trained, 44.4% were given increasing autonomy to use the technology. Further, 67.1% of trainees do not feel comfortable using robotic technology; however, 71.4% believe robotics has the potential to facilitate their education. Over 90% believe that robotic technology is here to stay. While residents have legitimate concerns about robotic implementation in orthopaedics, the majority of residents and fellows believe robotics will be a part of the future. However, few feel they receive adequate training or experience with the technology.
Keywords: robotics; orthopaedics; residency training; technology; surgical training; survey